Broadband X-ray spectral and timing properties of the accreting millisecond X-ray pulsar IGR J17498−2921 during the 2023 outburst - Li, Z. S.; Kuiper, L.; Pan, Y. Y.; Falanga, M.; Poutanen, J.; Chen, Y. P.; Xu, R. X.; Ge, M. Y.; Huang, Y.; Song, L. M.; Zhang, S.; Lu, F. J.; et al. (EDP Sciences, 2025)
We report on the broadband spectral and timing properties of the accreting millisecond X-ray pulsar IGR J17498‑2921 during its April 2023 outburst. We used data from NICER (1–10 keV), NuSTAR (3–79 keV), Insight-HXMT (2–150 keV), and INTEGRAL (30–150 keV). We detected significant 401 Hz pulsations across the 0.5–150 keV band. The pulse fraction increases from ∼2% at 1 keV to ∼13% at 66 keV. We detected five type-I X-ray bursts, including three photospheric radius expansion bursts, with a rise time of ∼2 s and an exponential decay time of ∼5 s. The recurrence time is ∼9.1 h, which can be explained by unstable thermonuclear burning of hydrogen-deficient material on the neutron star surface. The quasi-simultaneous 1–150 keV broadband spectra from NICER, NuSTAR and INTEGRAL can be aptly fitted by an absorbed reflection model, relxillCp, and a Gaussian line of instrumental origin. The Comptonized emission from the hot corona is characterized by a photon index Γ of ∼1.8 and an electron temperature kTe of ∼40 keV. We obtained a low inclination angle i ∼ 34°. The accretion disk shows properties of strong ionization, log(ξ/erg cm s‑1)∼4.5, over-solar abundance, AFe ∼ 7.7, and high density, log(ne/cm‑3)∼19.5. However, a lower disk density with normal abundance and ionization could also be possible. Based on the inner disk radius of Rin = 1.67RISCO and the long-term spin-down rate of ‑3.1(2)×10‑15 Hz s‑1, we were able to constrain the magnetic field of IGR J17498‑2921 to the range of (0.9 ‑ 2.4)×108 G.